(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, there are many countries in the world, but in this world our unique native land and Uzbekistan are one and only. The uniqueness of the so-called Uzbekistan is manifested in its unique nature, rich history, hardworking people, as well as the fact that representatives of different nationalities and nationalities live on this land as children of a single family. Such harmony, friendship and cooperation also have their deep historical roots and foundation.